PENINGKATAN PENGETAHUAN IBU BALITA TENTANG STUNTING MELALUI EDUKASI TERSTRUKTUR DI DESA PONDOK: STUDI PRE-TEST DAN POST-TEST - Luthfia Nur Safira; Agil Setia Putri; Dwi Bayu Saputro; Anida Nasywa Salsabila; Ayu Wulan Dari; Alya Anugrahayu Brilianti; Vina Astuti; Andi Muhammad Zaki; Sudrajah Warajati Kisnawaty; Adisty Rose Artistin (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2026)
The problem faced by partners in this community service activity is the high rate of stunting in Pondok Village, Grogol District, Sukoharjo, Central Java, and the lack of knowledge among mothers of toddlers about stunting and its prevention, which has an impact on the suboptimal practice of complementary feeding and monitoring of child growth and development. The proposed solution is structured education through interactive lectures and educational materials such as posters and power point presentations, ai med at enhancing mothers knowledge and awareness regarding stunting prevention. The method used was a pre-test and post-test to measure the increase in knowledge, as many as 30 participants who were mothers of toddlers were targeted in this activity. The results showed an average increase in participants knowledge scores from 81,32% in the pre-test to 92,44% in the post-test, a difference of 11,12%. The evaluation of the activity revealed high enthusiasm among participants and an improvement in understanding, which is expected to encourage behavioral changes related to child nutrition and stunting prevention. The conclusion of this activity is that structured education has proven effective in increasing the knowledge of mothers of toddlers about stunting. Suggestions for the sustainability of this activity are strengthening community-based education networks so that mothers can become information agents in their environment.